Measuring the interest rate and exchange rate risk of a commercial bank's portfolio - Monica Ahlstedt (Bank of Finland, 1990)
The Bank of Finland, in accordance with its regulations, is responsible for the stability of the financial markets. The main actors in the Finnish financial markets are fourteen authorized foreign,exchange banks. The Bank of Finland has therefore set up a risk monitoring system to measure the'risk exposures taken by these banks.
URN:NBN:fi:bof-201807311808
Keywords: 330